The Relationship Financial Statements Components and Audit Fees in Developing Countries - Farzaneh Nasirzadeh; Qassim Herez (Iranian Journal of Accounting, Auditing & Finance)
The present study is concerned about the relationship between the cash flow statement and payment balance sheet of listed companies on the Iraq Stock Exchange, compared with the conducted studies on the Tehran Stock Exchange. In other words, the present study attempts to figure out whether or not the change of cash flow statement items and balance sheets can lead to an increase or decrease in the changes in audit fees.The multivariable regression model was used for hypothesis testing. Research hypotheses were tested using a 774 firm-year sample on the Tehran Stock Exchange and 210 firm-year on the Iraq Stock exchange during 2012-2017 using multiple regression models based on the mixed data technique.The obtained results indicate that there is a significant relationship between the change of cash flow statement items and balance sheet and audit fees, which means the relationship between changes in debts, assets, dividends, operational, investment, and financing cash flow and tenure, audit fee, and auditor change is significant.  The current study is the first study that compares the relationship between cash flow statement items and balance sheet and audit fee of listed companies on the (Iran and Iraq) stock exchange, so this study contributes to the development of knowledge in this field.